A Legal Review of Mediations That Appear to be Successful But end in Failure - Christian Lasro Berto Siagian; Mulida Hayati; Nuraliah Ali (Eduvest - Journal of Universal Studies, 2025)
Mediation has become one of the increasingly popular dispute resolution methods in the modern legal system because it is considered a faster, more efficient, and more cost-effective solution than litigation. However, the success of mediation cannot always be guaranteed. Some cases show that mediation, which seemed to work well at first, ended without reaching a binding agreement. This study aims to analyze the causes of mediation failures that seem to be successful but end up failing. The research method used is a qualitative approach, with data collection through literature studies. After the data is collected, the analysis is carried out through the process of filtering, presenting information, and drawing conclusions. The results of the study revealed several main factors that led to mediation failure, including unclear or unrealistic agreements, excessively high expectations from one or both parties, external influences that interfere with the mediation process, and limitations of mediators in skills and neutrality. This study emphasizes the importance of a deep understanding of the factors that cause failure as well as appropriate preventive efforts to improve the success of mediation and reach mutually beneficial agreements.